Immunoglobulin mu-chain gene rearrangement in a patient with T cell acute lymphoblastic leukemia. - Ha, K (1984)
A 6-yr-old girl with T cell acute lymphoblastic leukemia (ALL) is described. She had a mediastinal mass and her leukemic cells expressed T cell-associated antigens (Leu 1+, OKT3+, OKT9+, and OKT10+). When we examined genomic DNA from the leukemic cells, we detected Ig mu-chain gene rearrangement with germ-line configuration of light chain genes. As reported recently, detecting Ig gene rearrangement has become an important procedure for further classifying B cell precursor cells. This case, however, suggests that there is also heterogeneity among patients with T cell ALL, not only at the level of cell surface phenotypes, but also at the level of the Ig gene. These findings have major implications when we consider both the ontogenesis of these leukemic cells and the normal differentiation of human lymphocytes.